Efektivitas Kapsul Ekstrak Buah Mengkudu (Morinda citrifolia L.) Terhadap Penurunan Kadar Glukosa Darah Mencit (Mus musculus L.) - Andita Nur Wijayanti (Jurnal Kesehatan Farmasi, 2022)
Empirical and research result proved that chemical contents of noni plant have medical benefits. Former research showed that noni fruit extract has antihyperglicemic effect. This research was aimed to determines the effectivity of noni fuit extract (Morinda citrofolia L.) capsule to lowering mice blood glucose level. This research was used glucose induced hyperglicemic mice with treatment groups such as: negative control group, noni fruit extractt capsule dose 1, and noni fruit extract capsule dose 2. Noni fruit extract capsule dose 1 treated group showed 40,7Â±10,8 mg/dl blood glucose level drop and 38,7Â±16,6 mg/dl drop for dose 2 treated group. The conclusion of this research is noni fruit extract capsule lowering mice blood glucose level.